Decreased competitive interactions drive a reverse species richness latitudinal gradient in subarctic forests. Issue 2 (1st February 2015) - Marshall, Katie E.; Baltzer, Jennifer L.
Abstract : The tendency for species richness to decrease toward the poles is one of the best‐characterized patterns in biogeography. The mechanisms behind this pattern have received much attention, yet very few studies have investigated very high‐latitude communities. Here, using data from 134 permanent sample plots from 60° to 68° N, we show that boreal forest plant communities in northwestern Canada increase in richness toward the poles, despite a strong increase in climatic harshness. We hypothesized three possible explanations for this pattern: (1) historical biogeography, (2) reduced competition for light at high latitudes (biotic interactions), and (3) changes in soil characteristics with latitude. We used multidimensional scaling to investigate the community composition at each site and found no clustering of communities by latitude, suggesting that historical biogeography was not constraining site diversity. We then investigated the mechanisms behind this gradient using both abiotic (climate and soil) and biotic (tree stand characteristics) variables in a multiple factor analysis. We found that the best predictor of species richness is an environmental gradient that describes an inverse relationship between temperature and tree‐stand density, suggesting that reduced competition for light due to reduced tree growth at low temperatures at higher latitudes allows greater species richness. This study shows that low energy availability and climatic harshness may not be limiting species richness toward the poles, rather, abiotic effects act instead on the strength of biotic interactions.